Development in PaCO2 over 12 months in patients with COPD with persistent hypercapnic respiratory failure treated with high-flow nasal cannula—post-hoc analysis from a randomised controlled trial. Issue 1 (18th November 2020) - Storgaard, Line Hust; Hockey, Hans-Ulrich; Weinreich, Ulla Møller
Abstract : Introduction: Persistent hypercapnic failure in chronic obstructive pulmonary disease (COPD) is associated with poor prognosis. Long-term home non-invasive ventilation is recommended for patients with PaCO2 >7.0 kPa. Domiciliary high-flow nasal cannula (HFNC) reduces PaCO2 in short-term studies. This post-hoc analysis examines the effect of HFNC on PaCO2 levels, exacerbations and admissions in patients with COPD with persistent hypercapnic and hypoxic failures. Methods: The original trial included 74 long-term oxygen-treated patients (31 HFNC treated/43 controls) with persistent hypercapnic failure (PaCO2 >6 kPa) who completed the 12-month study period. Baseline data included age, sex, blood gases, exacerbations and hospital admissions in the previous year. Data on blood gases were also recorded at 6 and 12 months for all patients. In addition, acute changes in blood gases after 30 min of HFNC use at site visits were examined, as were exacerbations and hospital admissions during study. Results: Patients were comparable at baseline. After 12 months there was a 1.3% decrease in PaCO2 in patients using HFNC and a 7% increase in controls before HFNC use on site (p=0.003). After 30 min of HFNC at visits PaCO2 changed significantly, with comparable reductions, at 0, 6 and 12 months, including for controls who tried HFNC at study end (p<0.001). The exacerbation rate increased, compared with 12 months prestudy, by 2.2/year for controls (p<0.001) and 0.15/year for HFNC-treated patients (p=0.661). Hospital admission rates increased in the control group, +0.3/year from prestudy (p=0.180), And decreased by 0.67/year (p=0.013)for HFNC-treated patients. Conclusion: This post-hoc analysis indicates that HFNC stabilises patients with COPD with persistent hypoxic and hypercapnic failures, in terms of PaCO2, exacerbations and number of hospitalisations, whereas those not receiving HFNC worsened. This suggests that HFNC is a possible treatment for patients with persistent hypercapnic COPD.